한반도 인근의 미세먼지 시공간 농도 변화 연구 - 이찬주(Chan-Joo Lee); 홍민선(Min-Sun Hong) (한국대기환경학회지(국문), 2019)
In this study, spatiotemporal variations of fine particulates were analyzed using published data of PM2.5 and PM10 from 2001 to 2018 in and near the Korean peninsula coupled with upper (850 hPa) wind vectors. Six sites were chosen, two in remote islands, three in the Seoul metropolitan area and one on East Coast to investigate hourly, monthly and annual variations of fine particulates. Other than the above six sites, 5 more sites were chosen each along the West and East Coast of the Korean peninsula to investigate the hourly variations of fine particulates. Data were analyzed using Pandas, Seaborn, Windrose module in Python. PM2.5 concentrations are higher than annual ambient standards, 15 μg/m3 and PM10 concentrations were more related to man-made emission sources compared to PM2.5. Hourly variations of PM10 and PM2.5 at West Coast cities are apparantly different from those located along the East Coast of the Korean peninsular Upper air data analysis in remote islands shows that transboundary transport of fine particulates from China and the Korean peninsula are comparable to each other. KCI Citation Count: 0